Non compacted miocardiopathy associated with congenital heart Defects. Case report Hnerm-Essalud: Miocardiopatía no compactada asociada a Defectos cardiacos congénitos. Reporte de caso Hnerm-Essalud - Catalán, Ismael (2019)
The present case corresponds to a 1-month-old male patient with a diagnosis of non-compacted cardiomyopathy associated with congenital heart defects. Noncompacted cardiomyopathy is newly included by the AHA as its own since the second half of the last decade. The diagnosis is mainly echocardiographic. Symptoms in children under one year may start with heart failure. The evolution is variable and tends to improve in some cases. Finally, in later decades, heart failure, thromboembolic events, malignant arrhythmias and sudden death become more pronounced. The management is in medicines for heart failure, to avoid malignant arrhythmias and thromboembolic events.